GaAsBi: From Molecular Beam Epitaxy Growth to Devices. Issue 2 (21st February 2022) - Richards, Robert D.; Bailey, Nicholas J.; Liu, Yuchen; Rockett, Thomas B. O.; Mohmad, Abdul R.
Abstract : On the background of a molecular beam epitaxy (MBE) machine viewport, a simplified representation of the Bi surface hopping mechanism is depicted for a GaAs surface exposed to an oscillating Bi flux. The exact behaviour of Bi on a growing surface is still the subject of some debate and oscillating fluxes appear to enhance Bi incorporation, potentially due to the increased likelihood of Bi – Ga bonds forming. These mechanisms are discussed in the Review by Robert D. Richards, Abdul R. Mohmad, and co‐workers (see article number 2100330 ).